2018
DOI: 10.1111/1467-9566.12660
|View full text |Cite
|
Sign up to set email alerts
|

Culturally embedded health beliefs, self‐care and the use of anti‐ageing medicine among Australian and Japanese older adults

Abstract: Adopting Kleinman's and Lock's ideas that there are cultural variations in understandings of health care and the medicalisation of ageing bodies, this study compares and contrasts older adults' use of anti-ageing medicine in two cultural settings. Based on 42 interviews conducted in Australia and Japan with adults aged 60 and over, findings revealed distinct pathways to initiating anti-ageing medicine use between the two cohorts which reflect different attitudes to the medicalisation of ageing in the two setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… 51 Several studies conducted in Australia have highlighted factors associated with CM use among healthy older people, namely personal beliefs and experiences, social networks, educational levels and previous experiences encountering conventional medicine. 52 , 53 …”
Section: Main Textmentioning
confidence: 99%
“… 51 Several studies conducted in Australia have highlighted factors associated with CM use among healthy older people, namely personal beliefs and experiences, social networks, educational levels and previous experiences encountering conventional medicine. 52 , 53 …”
Section: Main Textmentioning
confidence: 99%
“…Previous studies indicated that people’s attitudes toward dealing with pain [ 16 ], health beliefs, and self-care [ 17 ] varied due to differences in lifestyle and culture between Japan and other countries. Therefore, perceptions toward knee OA may also differ between Japan and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that people's attitude toward dealing with pain [14], health beliefs, and selfcare [15] were varied owing to differences in lifestyle and culture between Japan and other countries.…”
Section: Introductionmentioning
confidence: 99%